IMPROVING CHILDREN'S COGNITIVE USING THE TALKING STICK MODEL AND FLANELBOARD MEDIA IN GROUP B TK PERTIWI - Ratna Purwanti; maisyati mukaramah; Miftha Huljannah (E-CHIEF Journal, 2021)
This research is motivated by the low cognitive activity of children in recognizing number symbols. This is caused by one-way learning, monotonous and uninteresting. The purpose of this study was to describe cognitive aspects of the ability to recognize number symbols using the Talking stick model and the Flannel Board media at the PERTIWI Anjir Pasar TK Children. The research used a qualitative approach and the type of classroom action research with research subjects 4 boys and 5 girls group B TK PERTIWI Anjir Pasar. The study was carried out in 4 meetings with the result showing that applying the combination of the Talking stick model and the Flannel Board media can increase teacher activity up to 97%, children's activities reach 100% and children's cognitive development result reach 100%. The result of this study can be used as an alternative in the selection of model in developing children's cognitive abilities. Keywords: Cognitive, Numbers, Talking Stick, Flannel Board